Lysine malonylation and propionylation are prevalent in human lens proteins. (January 2020) - Nahomi, Rooban B.; Nandi, Sandip K.; Rakete, Stefan; Michel, Cole; Fritz, Kristofer S.; Nagaraj, Ram H.
Abstract: Acylated lysine residues represent major chemical modifications in proteins. We investigated the malonylation and propionylation of lysine residues (MalK, PropK) in the proteins of aging human lenses. Western blot results showed that the two modifications are present in human lens proteins. Liquid chromatography-mass spectrometry (LC-MS/MS) results showed 4–18 and 4–32 pmol/mg protein of MalK and PropK, respectively, in human lens proteins with no apparent changes related to aging. Mass spectrometry results revealed that MalK- and PropK-modified lysine residues are present in all major crystallins, other cytosolic proteins, and membrane and cytoskeletal proteins of the lens. Several mitochondrial and cytosolic proteins in cultured human lens epithelial cells showed MalK and PropK modifications. Sirtuin 3 (SIRT3) and sirtuin 5 (SIRT5) were present in human lens epithelial and fiber cells. Moreover, lens epithelial cell lysate deacylated propionylated and malonylated lysozyme. The absence of SIRT3 and SIRT5 led to higher PropK and MalK levels in mouse lenses. Together, these data suggest that MalK and PropK are widespread modifications in lens and SIRT3 and SIRT5 could regulate their levels in lens epithelial cells. Highlights: SIRT3 and SIRT5 are present in human lenses, and they are catalytically active in epithelial cells but not in fiber cells. Malonylation and propionylation of lysine residues occurs in human lens proteins and the levels of MalK and PropK do not change significantly during aging. The absence of SIRT3 and SIRT5 leads to increased propionylation and malonylation proteins in mouse lenses.